Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3174/ajnr.a2727
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and Midterm Results following Treatment of Unruptured Intracranial Aneurysms with the Pipeline Embolization Device

Abstract: BACKGROUND AND PURPOSE:A number of flow-diverting devices have become available for endovascular occlusion of cerebral aneurysms. This article reports immediate and midterm results in treating unruptured aneurysms with the PED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
115
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(127 citation statements)
references
References 32 publications
7
115
1
3
Order By: Relevance
“…Adjunctive coil placement may enhance aneurysm thrombosis 56 . The results so far have been promising: Lylyk et al reported angiographically-documented occlusion rates of 56%, 93%, and 95% at three, six and 12 months respectively, whereas the investigators of the recently conducted Pipeline Embolization Device for the Intracranial Treatment of Aneurysms (PITA) trial reported a 93% occlusion rate at six months [56][57] . The porosity of the stent is thought to allow for continued blood flow through perforating arteries, given the demand of these vessels.…”
Section: Study Limitationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Adjunctive coil placement may enhance aneurysm thrombosis 56 . The results so far have been promising: Lylyk et al reported angiographically-documented occlusion rates of 56%, 93%, and 95% at three, six and 12 months respectively, whereas the investigators of the recently conducted Pipeline Embolization Device for the Intracranial Treatment of Aneurysms (PITA) trial reported a 93% occlusion rate at six months [56][57] . The porosity of the stent is thought to allow for continued blood flow through perforating arteries, given the demand of these vessels.…”
Section: Study Limitationsmentioning
confidence: 98%
“…Despite the initial widespread enthusiasm for the use of these devices in such cases, few reports on such usage have been published to date. For example, only 6% of the aneurysms in the PITA trial were located in the VBS 57 . In our clinical series, an initial complete occlusion or successful embolization was observed in all ten patients during the long-term follow-up period.…”
Section: Study Limitationsmentioning
confidence: 99%
“…The efficacy of this device, achieving a high aneurysm occlusion rate of 93%-94%, has made it a particularly appealing tool in endovascular neurosurgery. 20,21,25 The significant recurrence rate in previously treated aneurysms has prompted an increased use of the PED in these aneurysms as a second-line treatment. Despite the overwhelming efficacy in untreated aneurysms, initial experience demonstrated decreased efficacy in previously treated aneurysms with a reported 68.7% 20 complete occlusion rate and prior treatment as a predictor of PED treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…20,21,25 The significant recurrence rate in previously treated aneurysms has prompted an increased use of the PED in these aneurysms as a second-line treatment. Despite the overwhelming efficacy in untreated aneurysms, initial experience demonstrated decreased efficacy in previously treated aneurysms with a reported 68.7% 20 complete occlusion rate and prior treatment as a predictor of PED treatment failure. 22 While prior treatment failure certainly places the patient at risk for further recurrence, the PED provides a distinct advantage in restoring physiological cerebral flow dynamics and providing a scaffold for endothelialization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation